Occurrence of Rhabditid Nematodes in the Pet Giant African Land Snails (Achatina fulica) - d'Ovidio, Dario; Nermut, Jirí; Adami, Chiara; Santoro, Mario (Frontiers in Veterinary Science, 2019)
Gastropods comprise nearly 60,000 species of aquatic as well as terrestrial mollusks, primarily snails and slugs. The giant African land snail (Achatina fulica) is one of the most popular pet snails worldwide. This gastropod mollusk is known as the intermediate host of several parasites that cause severe diseases in pets, free-ranging vertebrates and humans. The aim of this survey was to investigate the occurrence of parasites in giant African land snails kept as pets in southern Italy. Fresh fecal samples were collected from a total of 60 giant African land snails kept in three private collections in Campania region (Italy). In addition, microscopic analysis of mucus and histological examination of biopsy samples from the foot muscle of 30 individual snails were performed. Coprological examination revealed the presence of rhabditid nematodes identified by both morphological and molecular assessment as Rhabditella axei in two out of three examined samples, and Rhabditis terricola, Cruznema sp., and Pristionchus entomophagus in one coprological sample. No parasites were detected in the muscle biopsy samples, or in the mucus. Due to the potential harm of rhabditid nematodes, their presence in giant African land snails potentially in contact with both pets and humans should not be disregarded.